2022
DOI: 10.51357/jei.v3i1.182
|View full text |Cite
|
Sign up to set email alerts
|

Examining Online Course Evaluations and the Quality of Student Feedback

Abstract: The purpose of this article was to provide a comprehensive review of research on the quality of student feedback from post-secondary institutions using online course evaluations versus traditional paper-pencil methods. Nineteen peer-reviewed articles published from 2000 to 2020 were examined for changes to course evaluations following a transition to online collection methods. Three themes emerged from the literature: effects on response rates, presence of non-response bias, and effects on comment quality. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…As such, the majority of the students did not participate in this exercise. This trend of result reflects the outcome of recent studies that have reported unit non-response as a common phenomenon in online surveys ( Marcham et al, 2020 ; Čehovin et al, 2022 ; Falk and Thies, 2022 ; Plante et al, 2022 ). Nevertheless, the recorded high unit non-response rates in this context cannot be entirely attributed to the transition from a paper-and-pencil survey to an online survey.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As such, the majority of the students did not participate in this exercise. This trend of result reflects the outcome of recent studies that have reported unit non-response as a common phenomenon in online surveys ( Marcham et al, 2020 ; Čehovin et al, 2022 ; Falk and Thies, 2022 ; Plante et al, 2022 ). Nevertheless, the recorded high unit non-response rates in this context cannot be entirely attributed to the transition from a paper-and-pencil survey to an online survey.…”
Section: Discussionsupporting
confidence: 79%
“…This transition has also led to decreased rates of student participation, resulting in high rates of non-response ( Dillman et al, 2002 ). Several studies have shown that unit non-response (i.e., individuals not responding to any item on the survey instrument or complete non-participation) in online evaluation surveys is a key challenge for the introduction of technology in students’ appraisal of teaching and learning ( Guder and Malliaris, 2013 ; Marcham et al, 2020 ; Čehovin et al, 2022 ; Falk and Thies, 2022 ; Plante et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-learning Satisfaction Questionnaire, ELSQ (Cofini, et al, 2022) Course evaluation (Kuch & Roberts, 2018) End-Of-Course Evaluations, EOCE (Plante et al, 2022) Students 'Evaluation of Educational Quality, SEEQ (Fatani, 2020) Limitations: monocriteria, qualitative presentation of data, contextuality (program-or course-driven), subjective method of diagnosis.…”
Section: Engagement and Satisfactionmentioning
confidence: 99%